Efisiensi Dari Metode Transplantasi Rumput Laut Pada Kawasan Bekas Penambangan Timahdi Pantai Teluk Kabupaten Bangka - Umroh Umroh; Eva Utami (Akuatik: Jurnal Sumberdaya Perairan, 2014)
Waters of Bangka Island condition increasingly polluted and marine ecosystems all the time more damage due to the impact of offshore tin mining. Offshore tin mining destruct marine ecosystem and always leaves the turbidity and high sedimentation rates in the ocean. Mining of floating cause the seabed sediments are mixed with sea water, as a result suspended matter content become higher and spreading by ocean waves into seagrass ecosystems. High sedimentation rate if it exceeds the threshold, in addition to inhibiting seagrass photosynthesis, can also cause death and loss of seagrass. Seagrass has several important functions in coastal and marine areas, such as spawning, protection and enlargement ground of marine life. Seagrass bed has a very important role, therefore the seagrass damage that occurs needs to be fixed, one of the method is seagrass transplantation as restoration efforts. The aim of research was to determined the efficiency of seagrass transplantation method in accordance with waters of Bangka Island,at tin post mining in the sea post. Seagrass transplantation method used as experimental in this research is a method of burlap sacks and Sprig Anchor. The results showed that the method is more suited to waters of Bangka Island. It is because Bangka island waters classified as fast-flowing waters. The method of burlap sacks is a method that fill sacks with substrate, so could be used as retaining current